2012
DOI: 10.2166/hydro.2012.150
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of 3D flow at right-angled confluences with and without upstream planform curvature

Abstract: The purpose of this paper is to study the individual and combined effect of upstream planform curvature and difference in bed elevations at the tributary entrance to the confluence on the flow in the confluence hydrodynamics zone. To do this, flow at right-angled confluences with three planforms and four values of bed elevation discordance ratio (Δz T /h d ) is simulated using a threedimensional (3D) numerical model. Three confluence planforms include confluences with the (1) straight tributary canal (SC), (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The results show the importance of junction angle and tributary entry location on flow structure and bed morphology, providing the basis for elaboration of a conceptual model of the dynamics of confluent meander bends based on previous experimental, field, and numerical modeling studies (Roberts, 2004;Riley and Rhoads, 2012). The findings are also consistent with relationships between junction angle and hydrodynamic conditions for asymmetrical and symmetrical confluences (Mosley, 1976;Best, 1987), and show that flow conditions inherited from upstream channel curvature are reflected in the structure of flow within confluent meander bends on large riversconfirming results of experimental work (Dordević, 2013) and of field studies at a small natural confluent meander bend (Riley and Rhoads, 2012). Strong flow deflection at the high-angle confluent meander bend augments helical motion inherited from flow curvature through meander bends in the main and tributary channels upstream of the junction, producing twin surface-convergent, counter-rotating helical cells through the downstream channel that vary in relative size with changes in M r .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The results show the importance of junction angle and tributary entry location on flow structure and bed morphology, providing the basis for elaboration of a conceptual model of the dynamics of confluent meander bends based on previous experimental, field, and numerical modeling studies (Roberts, 2004;Riley and Rhoads, 2012). The findings are also consistent with relationships between junction angle and hydrodynamic conditions for asymmetrical and symmetrical confluences (Mosley, 1976;Best, 1987), and show that flow conditions inherited from upstream channel curvature are reflected in the structure of flow within confluent meander bends on large riversconfirming results of experimental work (Dordević, 2013) and of field studies at a small natural confluent meander bend (Riley and Rhoads, 2012). Strong flow deflection at the high-angle confluent meander bend augments helical motion inherited from flow curvature through meander bends in the main and tributary channels upstream of the junction, producing twin surface-convergent, counter-rotating helical cells through the downstream channel that vary in relative size with changes in M r .…”
Section: Resultssupporting
confidence: 80%
“…However, previous field observations and studies of tributary development in meandering river systems suggest that tributaries preferentially join main channels along the outer bank of bends (Callaway, 1902;Davis, 1903;Flint, 1980;Hills, 1983;Abrahams, 1984aAbrahams, , 1984b, forming confluent meander bends. Recent work has also shown that inherited flow conditions from upstream channel curvature can influence the structure of flow within confluences (Dordević, 2013) and at bifurcations (Kleinhans et al, 2013). Recent work has also shown that inherited flow conditions from upstream channel curvature can influence the structure of flow within confluences (Dordević, 2013) and at bifurcations (Kleinhans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these conceptual models are physically combined, as shown in Figure 4. Field investigations [5,21,22], laboratory experiments [6,[23][24][25], and numerical simulations [14,[26][27][28][29][30], complementing each other, are common methods to help understand the morpho-dynamics of a confluence. Bradbrook [31] suggested that combining all three methods would help to understand the confluences more comprehensively.…”
Section: Items Non-tidal Confluence Tide-driven Confluencementioning
confidence: 99%
“…[6] proposed a theoretical flow pattern according to the experimental observations in that study. Thereafter, the impacts of flow confluences at different channel junctions on the flow pattern and structures were widely investigated through various numerical and experimental studies in the past decades (e.g., [7][8][9][10][11][12][13][14][15][16][17][18][19][20]). All the results of these studies have shown and evidenced that the flow junctions with different properties (e.g., size ratio, angle and water depth change due to concordant/discordant bed) could affect greatly the characteristics of the flow pattern and structures and thus the hydrodynamic responses at the confluence zone, with indicating that the effects of the flow junctions and characteristics have to be considered and included in the hydraulic modeling process so as to obtain better physical interpretations and accurate numerical predictions.…”
Section: Introductionmentioning
confidence: 99%